SELF DISCLOSURE PEKERJA SEKS KOMERSIAL LADY BOY DALAM APLIKASI TINDER DI KABUPATEN BADUNG, BALI - Pradevi, Rinjani; Sugiarica Joni, I Dewa Ayu; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2020)
ABSTRACT   As a  tourist  destination,  Bali  has an impact  on  the presence  of  entertainment  needs for tourists, one of which is prostitution. It is clear in Bali that prostitution is now shifting to social media,  furthermore  sex  workers are  also  ladyboy.  One form  of  the social  media  that  is commonly used is the Tinder. One of the important aspects in the use of social media is self- disclosure.  Research in this  area commonly  uses descriptive  qualitative  research, with  data collection techniques through interviews. The results showed that the informants in this study claimed  to  openly  carry out  their  self-disclosure  process.  However, using  an onion  layer model,   not   all   stages   were  passed  by   the  informants.   Informants   in   this   study  also experienced  a process of  de-penetration  when their  Tinder  matches did  not  accept their identity   as  ladyboy.   Physical   appearance  and  communication   strategies   are  key  for informants to attract the attention of their Tinder matches.   Keywords: Self-disclosure, ladyboy, social penetration, tinder.